Design, Synthesis, Antinociceptive and Anti-Inflammatory Activities of Novel Piroxicam Analogues - Amanda Silva de Miranda; Walfrido Bispo Júnior; Yolanda Silva; Magna Suzana Alexandre‐Moreira; Rosane Nora Castro; J.R. Sabino; Luciano M. Lião; Lı́dia Moreira Lima; Eliezer J. Barreiro (2012)
In this paper we report the design, synthesis, antinociceptive and anti-inflammatory activities of a series of benzothiazine N-acylhydrazones 14a–h, planned by structural modification of piroxicam (1), a non steroidal anti-inflammatory drug. Among the synthesized analogues, compounds 14f (LASSBio-1637) and 14g (LASSBio-1639) were identified as novel antinociceptive and anti-inflammatory prototypes, active by oral administration, acting by a mechanism of action that seems to be different from that of piroxicam, since they were inactive as an inhibitor of cyclooxygenase (COX-1 and COX-2) at concentrations of 10 mM.